Legal Responsibility in Smart Contracts in Blockchain Transactions - Aslina, Neri; Noviya, Anis (Ipso Jure, 2026)
The development of blockchain technology has given rise to smart contracts as a self-executing, decentralized, code-based contractual mechanism. Their presence poses conceptual and normative challenges in the Indonesian contract law system, particularly regarding the legal standing and construction of the parties' responsibilities amidst a normative vacuum. This study aims to analyze the legal status of smart contracts from the perspective of Indonesian civil law and to formulate a relevant legal liability model for blockchain-based transactions. The research method used is normative legal research with statutory, conceptual, and analytical approaches. Primary legal materials include the Civil Code, the Electronic Transactions and Transactions Law, and regulations related to electronic transactions, while secondary legal materials include doctrine, liability theory, and literature on blockchain. The results show that smart contracts can be qualified as agreements as long as they meet the valid requirements of an agreement as stipulated in Article 1320 of the Civil Code. However, their immutable and automated nature creates tensions with the principles of freedom of contract and good faith. The identification of legal subjects in the blockchain ecosystem includes users, developers, validators, and platforms, with liability models that can be based on fault liability or the possibility of strict liability under certain conditions. The absence of norms has the potential to give rise to disparities in interpretation and legal uncertainty, so that a normative reconstruction is needed that is adaptive to the character of decentralization to ensure legal certainty, justice, and benefits.